L'analyse du Panafricanisme dans la littérature africaine d'expression française: étude de Les Soleils des Indépendances d'Ahmadou Kourouma - Batubenga David-Roger, Ndaye (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Analysis of pan-Africanism in French African literature: case study of The Suns of independences by Ahmadou Kourouma. (L'analyse du Panafricanisme dans la littérature africaine d'expression française : étude des Soleils des Indépendances d'Ahmadou Kourouma) This study seeks to analyse the concept of pan-Africanism in French African Literature as depicted in The Suns of independences by Ahmadou Kourouma. The theme as well as the plot of the novel are both part of the post-colonial era, when African states acceded to the so-called national sovereignty. Theoretically, this was the end of colonization. Indeed, the advent of independence in Africa was, among other things, the fulfilment of one of the objectives of the pan-Africanism movement. Those objectives, according to Estanilas Ngodi (2003:6), were to promote the well-being as well as the unity of African people and those of African descendants around the world; to ensure equal civic rights for African people; to ensure the total abolition of all forms of racial discrimination; and to demand a self-determination and genuine independence of and for African's people and states. To understand this challenging concept of pan-Africanism, we will draw inspiration from the studies of Edward Wilmot Blyden (1832-1912) who defined it as emerging a distinctive African personality: It is accepted in this study that the manner in and the extent to which the concept of pan-Africanism will be analysed should not be confused with other concepts such as Negroism or Negritude. The concern of asserting African history and identity by African people is justified by the fact that for centuries the philosophical and anthropological Eurocentric trend that Africans and their cultures and knowledge had no value. For this purpose, Trevor Roper (1963:871) asserted: "Perhaps in the future, there will be some African history, but at present, there is none; only the history of Europeans in Africa. The rest is darkness"¦and darkness is not a subject of history"¦" This denial of African history and civilization was, according to Europeans, the reason for the slave trade and colonization, and the development of pan-Africanism was the reaction or resistance against these views. That is the reason why, in the novel (The Suns of 4 independences), Kourouma depicts the concept of pan-Africanism and reveals the need for African people to assert themselves in humanity as being equal to all other races. Indeed, the advent of independence in Africa was an opportunity for Africans to regain their pre-colonial roots. Because it raised hopes and expectations to see Africa being led by its own sons. Unfortunately, independences have become a missed rendezvous or a disappointment for Africans. This argument is confirmed by the metaphor of Fama, a traditional king in the post-independence Africa: find himself "dried and undressed by colonization and Independences" (p.116). Broadly speaking, Kourouma interrogates the evolution of African societies in the light of pan-Africanism and denounces political, economic, and social issues that are affecting Africa in the post-colonial era. These issues include dictatorship, mismanagement, corruption, poverty, and the challenge of regaining African personality from colonial influence. What differentiates my study from the previous research is that I seek to investigate to which extent Kourouma portrays the failure of African society in the light of pan-Africanism before and after the colonialist era, and the impact of this failure upon the establishment of the pan-Africanist vision in Africa. Little attention has been given to the analysis of this novel (The Suns of independences) in this perspective. Kourouma is an Ivorian writer. In 1970, he published his first novel (The Suns of Independences) which is considered as a masterpiece in French African Literature and which many critics have classified it as one of the founding works in African Literature. In this study, in accordance with the novel above-mentioned I have considered three different aspects of pan-Africanism. Firstly, I described pan-Africanism as the search for the dignity of black people. Secondly, I examined it as the desire of regaining or rebuilding the African unity (African states without colonial borders). Thirdly, I analysed it as the return of African people to their history, their origin, and their cultural identity, in short, the return of Africa to its original state before the slave trade and colonization.
Keywords: African literature (French) -- History and criticism; Kourouma, Ahmadou -- Soleils des indépendances; Pan-Africanism in literature; Postcolonialism in literature; Africans in literature; Identity (Philosophical concept) in literature; Ethnicity in literature